2018
DOI: 10.1016/j.fertnstert.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial scratch injury for women with one or more previous failed embryo transfers: a systematic review and meta-analysis of randomized controlled trials

Abstract: The ESI may improve IVF success in patients with two or more previous ET failures undergoing fresh ET. The ESI timing and technique seem to play a crucial role in determining its effect on embryo implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 58 publications
(161 reference statements)
4
62
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10]26,27 The statement above has also been proved by several recent meta-analysis studies. 10,14 However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt. 15,16 Therefore, the clinical application of EI is still in controversial, especially for the frozen-thawed ET process due to the lack of evidence.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…[2][3][4][5][6][7][8][9][10]26,27 The statement above has also been proved by several recent meta-analysis studies. 10,14 However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt. 15,16 Therefore, the clinical application of EI is still in controversial, especially for the frozen-thawed ET process due to the lack of evidence.…”
Section: Discussionmentioning
confidence: 86%
“…The majority of EI trials have found that EI in luteal phase increased the IVF success rate . The statement above has also been proved by several recent meta‐analysis studies . However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[9][10][11] Vitagliano et al showed improved reproductive outcomes in women with two or more previous failed cycles, with the greatest beneficial effect seen when double luteal EI was performed. 10 Van Hoogenhuijze et al found improved CPR but no improved LBR in women with at least two previous failed cycles, concluding that it is still unclear whether EI improves IVF outcomes. 9 In line with this meta-analysis, Gui et al did not find any significant difference in CPR or LBR when including only RCT in their analysis.…”
mentioning
confidence: 99%